2018
DOI: 10.1002/bit.26516
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and cytosolic delivery of a native regulatory protein and its variants for modulation of ERK2 signaling pathway

Abstract: The modulation of a cell signaling process using a molecular binder followed by an analysis of the cellular response is crucial for understanding its role in the cellular function and developing pharmaceuticals. Herein, we present the modulation of the ERK2-mediated signaling pathway through the cytosolic delivery of a native regulatory protein for ERK2, that is, PEA-15 (phosphoprotein enriched in astrocytes, 15 kDa), and its engineered variants using a bacterial toxin-based delivery system. Based on biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The delivery platform is composed of a targeting moiety, translocation domain, and PEA15 derivative. The successfully developed rEgH9 and TDP were utilized by Ryou et al [ 18 ] as an effective tool for cytosolic delivery of cargo proteins in an EGFR-specific manner, implying broad uses for cancer therapy. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The delivery platform is composed of a targeting moiety, translocation domain, and PEA15 derivative. The successfully developed rEgH9 and TDP were utilized by Ryou et al [ 18 ] as an effective tool for cytosolic delivery of cargo proteins in an EGFR-specific manner, implying broad uses for cancer therapy. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the mid-2000s, cells were often fixed prior to observation by fluorescence microscopy, in part to improve resolution. These fixation conditions ranged from mild (4% paraformaldehyde) to harsh (methanol). , A historically relevant example is the discussion of fixation artifacts in the measurement of the delivery efficacy of VP22, a type I herpes simplex virus tegument protein . Results suggested that a greater degree of internalization was observed with methanol fixation as compared to paraformaldehyde fixation.…”
Section: Artifacts and Misinterpretations In Measurements Of Total Ce...mentioning
confidence: 99%
“…The Stx2B-ETAII chimera has been developed and successfully used to deliver EGFP, certain enzymes, and an ERK2 kinase regulator, and has proven to be more stable when fused to cargo proteins than Stx2B alone. 29,30 Here, we describe and validate the receptor-specific cytoplasmic delivery of VHL−monobody fusion proteins to cancer cells using a chimeric toxin delivery system, resulting in targeted degradation and signaling inhibition.…”
mentioning
confidence: 99%
“…Following furin protease cleavage within the ETA-II domain, the C-terminal portion reaches the cytosol via the Golgi apparatus and the endoplasmatic reticulum (ER) (see Figure a). The Stx2B-ETAII chimera has been developed and successfully used to deliver EGFP, certain enzymes, and an ERK2 kinase regulator, and has proven to be more stable when fused to cargo proteins than Stx2B alone. , …”
mentioning
confidence: 99%